2021
DOI: 10.1002/ajim.23246
|View full text |Cite
|
Sign up to set email alerts
|

Gender differences in experience and reporting of acute symptoms among cleaning staff

Abstract: Background Cleaning tasks pose risks of hazardous chemical exposure and adverse health effects for cleaning workers. We examined gender differences among cleaning staff in the experience of chemical‐related symptoms and in reporting to supervisors. Methods We analyzed cross‐sectional reports from 171 university hospital or campus cleaning staff on chemical exposures to cleaning products, experience of acute symptoms, reporting of symptoms to supervisors, as well as demographic and psychosocial factors (risk pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 50 publications
(175 reference statements)
0
3
1
Order By: Relevance
“…Our ndings showed that a substantial number of NAs with a WRMSD (84.4%) did not report it to their management. This gure is higher than reporting rates in previous studies that ranged from 21-74% [13,17,18,35,36]. WRMSD reporting to management was related to positive attitudes toward reporting, experience of witnessing the injury reporting of others, good safety climate, and not having WRMSDs resulting in changed of jobs, tasks, or work due to WRMSDs.…”
Section: Discussioncontrasting
confidence: 54%
See 2 more Smart Citations
“…Our ndings showed that a substantial number of NAs with a WRMSD (84.4%) did not report it to their management. This gure is higher than reporting rates in previous studies that ranged from 21-74% [13,17,18,35,36]. WRMSD reporting to management was related to positive attitudes toward reporting, experience of witnessing the injury reporting of others, good safety climate, and not having WRMSDs resulting in changed of jobs, tasks, or work due to WRMSDs.…”
Section: Discussioncontrasting
confidence: 54%
“…The U.S. Occupational Safety and Health Administration (OSHA) provides the legal foundation of employee's rights to report injuries free from retaliation and prohibits employers from taking any adverse actions against employees for the reporting [12]. However, there exist perceived barriers to reporting and many injuries or symptoms may go unreported [13,14]. Research indicated that 20-74% of U.S. workers who experienced a workrelated injury or symptom did not report it to their management [13,15].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our study found that reporting was affected by the intersection of gender and race/ethnicity. Previous studies have found women to be less likely than men to report 5,53 and BIPOC individuals to be less likely than Whites to report. 21 In our study, BIPOC men were more likely than non-Hispanic White women to report work-related low back pain, and a significant difference was observed only among those who sought health care.…”
Section: Individual Factorsmentioning
confidence: 80%